Alleviating acid inhibition via bentonite supplementation during acidulated swine manure anaerobic digestion: Performance enhancement and microbial mechanism analysis. (February 2023) - Hu, Fengping; Zhang, Shihao; Liu, Susu; Wan, Liping; Gong, Guijin; Hu, Tengfang; Wang, Xin; Xu, Li; Xu, Gaoping; Hu, Yuying
Abstract: Swine manure is usually transmitted by the "collection-storage-transport" mode of the biogas project. However, this particular application pattern results in high volatile fatty acids (VFAs) concentration due to the long transition time in the "collection-storage-transport" process. In this work, acidulated swine manure anaerobic digestion (AD) with bentonite supplementation was firstly investigated with an expectation of acid alleviation, performance enhancement and microbial mechanism. Results indicated that the methane production rate in the 20 g/L bentonite-added digester was 2.87 fold higher than that of the control digester. Chemical oxygen demand (COD) removal rate was elevated by 140.1% via bentonite supplementation. Besides, the rapid decrease of VFAs and ammonia indicated that bentonite supplementation could offer buffering capacity and alleviate acid inhibition. Microbial community analysis revealed that acetoclastic methanogenesis ( Methanosaeta and Methanosarcina ) was the predominant methanogenesis pathway in this AD system. Syntrophic acetate oxidation (SAO) bacteria were discovered in the bentonite-added digester, and they converted acetate into H2 /CO2 to support hydrogenotrophic methanogenesis. This study could offer guidance for acidulated swine manure AD in the practical biogas project. Graphical abstract: Image 1 Highlights: Bentonite was utilized for enhancing acidulated swine manure AD for the first time. Methane production rate at 20 g/L bentonite was significantly higher than at other dosages. Bentonite alleviated acid inhibition and enhancing buffering capacity. Syntrophic acetate oxidation bacteria were discovered in bentonite-added digester. Acetoclastic methanogenesis pathway was the predominant methanogenesis pathway.